2022
DOI: 10.1177/00380385221112246
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Practices of the Family Child

Abstract: Following the introduction of the influential ‘doing’ family perspective, an active understanding of parents has taken centre stage in sociological thinking on how families are constructed. However, this has not extended to children, and their roles as co-constructors of families have not received the same amount of attention. This article examines the practices children use to construct themselves as child of someone in relation to a parent. By locating children’s practices within the ‘doing’ family perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our work has a special interest in studies that stress the powerful concern in children's ethics for the welfare and care of others, including parents and other family members, friends, neighbours and pets (Frankel, 2017;Henze-Pedersen, 2022;Maftei & Holman, 2020;Martin et al, 2021;Siedlikowski et al, 2022;Tammi et al, 2020). This concern is expressed in a context of reciprocity and contingency, in which the children do not figure merely as passive receivers but as daily agents of care, thus going far beyond notions of them as 'caring children' or 'young carers', descriptions intended for somewhat exceptional circumstances (Henderson, 2012;Vergara et al, 2020a;Wihstutz, 2011).…”
Section: Ethics and Childhood In Childhood Studies And Feminist Studi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our work has a special interest in studies that stress the powerful concern in children's ethics for the welfare and care of others, including parents and other family members, friends, neighbours and pets (Frankel, 2017;Henze-Pedersen, 2022;Maftei & Holman, 2020;Martin et al, 2021;Siedlikowski et al, 2022;Tammi et al, 2020). This concern is expressed in a context of reciprocity and contingency, in which the children do not figure merely as passive receivers but as daily agents of care, thus going far beyond notions of them as 'caring children' or 'young carers', descriptions intended for somewhat exceptional circumstances (Henderson, 2012;Vergara et al, 2020a;Wihstutz, 2011).…”
Section: Ethics and Childhood In Childhood Studies And Feminist Studi...mentioning
confidence: 99%
“…At the same time, we can see that the results we have obtained that refer to children's emphasis on reciprocal care between parents and children are consistent with the findings of childhood studies in various sociocultural settings. This field has shown that children's ethics refer in particular to the welfare and care of others, especially of parents and other family members (Frankel, 2017;Henze-Pedersen, 2022;Martin et al, 2021;Siedlikowski et al, 2022). This field has also enabled a relational understanding of child agency, developed originally by authors like Mayall (2002), Brannen and Heptinstall (2003) and Brannen et al (2000).…”
Section: Introductionmentioning
confidence: 99%